Transition-Metal-Free, Visible-Light-Promoted C–S Cross-Coupling through Intermolecular Charge Transfer - Liu, Bin; Lim, Chern-Hooi; Miyake, Garret M. (Synlett, 2018)
C–S cross-couplings are an important class of reactions applied across organic synthesis, materials science, and pharmaceuticals. Several different methodologies have been developed to achieve this significant transformation. However, currently available synthetic procedures significantly rely on transition metals. This article describes historical developments in the field of transition-metal-catalyzed C–S cross-coupling reactions, the development of a visible-light-driven and catalyst-free approach to C–S bond formation, and future outlooks.
Keywords: C–S cross-coupling; transition-metal-free; photochemistry; charge transfer; late-stage functionalization; electron donor–acceptor complex